The Potential Role of Histone Modifications in Glioblastoma Therapy: Review Article - Mohammed A. Azab (MDPI AG, 2023)
Glioblastoma (GBM) is considered the most aggressive primary brain tumor. Recurrence after treatment is a significant problem with a failed response to optimal therapies. The recurrence of GBM is linked to different cellular and molecular pathways. Not only genetics are involved in gliomagenesis, but also epigenetics. Histone modulation through acetylation, phosphorylation, ubiquitination, and methylation can regulate gene expression and may play a role in the pathogenesis of GBM. Preclinical and clinical studies currently target epigenetic enzymes in gliomas, including a new generation of histone deacetylase (HDAC) inhibitors. Herein, I tried to highlight current research in glioma epigenetics, focusing on the culprit of histone modifications and the use of HDAC target therapies as a possible treatment line for glioblastoma.